2005
DOI: 10.1242/jeb.01857
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-activated potassium channel of the tobacco hornworm,Manduca sexta: molecular characterization and expression analysis

Abstract: Large-conductance calciumand voltage-gated potassium channels (BK or Slowpoke) serve as dynamic integrators linking electrical signaling and intracellular activity. These channels can mediate many different Ca 2+ -dependent physiological processes including the regulation of neuronal and neuroendocrine cell excitability and muscle contraction. To gain insights into the function of BK channels in vivo, we isolated a full-length cDNA encoding the alpha subunit of a Slowpoke channel from the tobacco hornworm, Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…Previous work using a Northern Blot assay has shown that Manduca sexta slowpoke (msslo) mRNA expression levels in thoracic dorsal longitudinal muscles (DLMs) are low from the fifth instar until P15 when they abruptly increase in the developing adult (Keyser and Witten, 2005). Using the more sensitive qPCR technique, we observed a similar developmental profile, with an abrupt 12.6-fold increase in msslo transcript levels, two-thirds through adult development on P15 (Fig.…”
Section: Msslo Mrna Levels Are Abruptly Upregulated In the Dlms Durinsupporting
confidence: 64%
See 4 more Smart Citations
“…Previous work using a Northern Blot assay has shown that Manduca sexta slowpoke (msslo) mRNA expression levels in thoracic dorsal longitudinal muscles (DLMs) are low from the fifth instar until P15 when they abruptly increase in the developing adult (Keyser and Witten, 2005). Using the more sensitive qPCR technique, we observed a similar developmental profile, with an abrupt 12.6-fold increase in msslo transcript levels, two-thirds through adult development on P15 (Fig.…”
Section: Msslo Mrna Levels Are Abruptly Upregulated In the Dlms Durinsupporting
confidence: 64%
“…Previous research using Northern Blot analysis revealed differential msslo transcript expression patterns during late adult development in the CNS and the DLMs. Although msslo is abruptly upregulated in the DLMs, it remains relatively low and only gradually increases in the CNS (Keyser and Witten, 2005). Using the more sensitive qPCR technique, we detected a 2.9-fold increase in CNS msslo expression at the PA stage (Fig.…”
Section: Msslo Mrna Levels Gradually Increase In the Cnsmentioning
confidence: 82%
See 3 more Smart Citations